Phase‐Modulation of Iron/Nickel Phosphides Nanocrystals "Armored" with Porous P‐Doped Carbon and Anchored on P‐Doped Graphene Nanohybrids for Enhanced Overall Water Splitting. (13th May 2021) - Wang, Lei; Fan, Jiayao; Liu, Ying; Chen, Mingyu; Lin, Yue; Bi, Hengchang; Liu, Bingxue; Shi, Naien; Xu, Dongdong; Bao, Jianchun; Han, Min
Abstract: Transition metal phosphides (TMPs) nanostructures have emerged as important electroactive materials for energy storage and conversion. Nonetheless, the phase modulation of iron/nickel phosphides nanocrystals or related nanohybrids remains challenging, and their electrocatalytic overall water splitting (OWS) performances are not fully investigated. Here, the phase‐controlled synthesis of iron/nickel phosphides nanocrystals "armored" with porous P‐doped carbon (PC) and anchored on P‐doped graphene (PG) nanohybrids, including FeP–Fe2 P@PC/PG, FeP–(Ni x Fe1‐ x )2 P@PC/PG, (Ni x Fe1‐ x )2 P@PC/PG, and Ni2 P@PC/PG, are realized by thermal conversion of predesigned supramolecular gels under Ar/H2 atmosphere and tuning Fe/Ni ratio in gel precursors. Thanks to phase‐modulation‐induced increase of available catalytic active sites and optimization of surface/interface electronic structures, the resultant pure‐phase (Ni x Fe1‐ x )2 P@PC/PG exhibits the highest electrocatalytic activity for both hydrogen and oxygen evolution in alkaline media. Remarkably, using it as a bifunctional catalyst, the fabricated (Ni x Fe1‐ x )2 P@PC/PG|| (Ni x Fe1‐ x )2 P@PC/PG electrolyzer needs exceptional low cell voltage (1.45 V) to reach 10 mA cm −2 water‐splitting current, outperforming its mixed phase and monometallic phosphides counterparts and recently reported bifunctional catalysts based devices, and Pt/C|| IrO2 electrolyzer. Also, such (Ni x Fe1‐ x )2 P@PC/PG|| (Ni x Fe1‐ x )2 P@PC/PG device manifests outstanding durability for OWS. This work may shed light on optimizing TMPs nanostructures by combining phase‐modulation and heteroatoms‐doped carbon double‐confinement strategies, and accelerate their applications in OWS or other renewable energy options. Abstract : Phase modulation of iron/nickel phosphides nanocrystals "armored" with porous P‐doped carbon (PC) and anchored on P‐doped graphene (PG) nanohybrids are realized, and the phase‐dependent electrocatalytic behaviors are observed. When employed in overall water splitting, the pure‐phase (Ni x Fe1‐ x )2 P@PC/PG only requires 1.45 V to reach 10 mA cm −2 water‐splitting current, outperforming its mixed‐phase and monometallic phosphides counterparts, and other reported bifunctional electrocatalysts.